Cholesterol- and blood-pressure-lowering drug use for secondary cardiovascular prevention in 2004–2013 Europe. (March 2017) - Achelrod, Dmitrij; Gray, Alastair; Preiss, David; Mihaylova, Borislava
Background: Suboptimal use of cardiovascular prevention medications has been reported. We report recent trends in secondary cardiovascular disease prevention drug use in Europe. Design: We used the 2004-2013 data from the Survey of Health, Ageing and Retirement in Europe (SHARE), a large longitudinal cohort study in middle-aged and elderly Europeans. Methods: Cross-sectional and panel data logistic regression models were used to study trends in cholesterol- and blood pressure-lowering drug use and effects of participant characteristics on the likelihood of drug use among participants with histoty of cardiovascular disease in SHARE. Results: In SHARE 21, 388 participants reported history of cardiovascular disease and provided data on cholesterol- and blood pressure-lowering drug use. At initial report, 40% and 60% of them used cholesterol- or blood pressure-lowering drugs, respectively. Increasing cross-sectional time trends were observed for both medication classes (odds ratios of use in 2013 vs . 2004, 1.6 (95% confidence interval 1.4–1.7) and 1.5 (1.4–1.6), respectively). However, among participants with multiple observations, the use of both classes declined over time (2013 vs . 2004 odds ratio 0.63 (0.51–0.77) and 0.68 (0.55–0.84), respectively; both trend p < 0.001), and with increasing duration since last cardiovascular event (odds ratio 0.74 (0.60–0.91), trend p = 0.01 and odds ratio 0.82 (0.66–1.03), trend p = 0.06, respectively for durations of nine years or more versus less than one year). Among people with history of cardiovascular disease, those obese, retired or with hypercholesterolaemia, hypertension, worse self-perceived health, and, in the case of lipid-lowering medication, with diabetes, were more likely to use these medications. Conclusions: Despite moderately increasing cross-sectional time trends, the use of secondary cardiovascular disease prevention drugs remains low in Europe with substantial discontinuation over time and with increasing duration from an acute cardiovascular event.